Perancangan SIM-Klinik Sistem Pengambilan dan Pengembalian Rekam Medis Di Klinik Jaya Kusuma Husada Kepanjen Kabupaten Malang - Anugrahanti, Wisoedhanie Widi; Maulana, Moh. (Politeknik Negeri Jember, 2024)
The Jaya Kusuma Husada Clinic in Kepanjen, Malang Regency, currently operates its medical records system manually, including the processes for retrieving and returning medical records. A Clinical Management Information System (SIM-Clinic) is necessary to support a more organized medical record management system, in accordance with the implementation of Minister of Health Regulation No. 24 of 2022. This study aims to design a SIM-Clinic for the medical record retrieval and return system. The research combines Research and Development (R&D) with descriptive analysis. Data collection was conducted through observation and interviews with 15 respondents, consisting of doctors, nurses, midwives, and medical record staff, selected through total sampling. The system design employed the waterfall methodology. The study results identified three categories of SIM-Clinic user needs: healthcare workers, medical record staff, and the head of the medical records department. The agreed system requirements have resulted in the development of a system flowchart, Data Flow Diagram (DFD), and Entity Relationship Diagram (ERD). It is recommended that the clinic prepare the necessary facilities, infrastructure, and healthcare human resources involved in the planned implementation of the medical record retrieval and return system through the SIM-Clinic.